2020
DOI: 10.7759/cureus.11555
|View full text |Cite
|
Sign up to set email alerts
|

Transaminases are Potential Biomarkers of Disease Severity in COVID-19 Patients: A Single-Center Experience

Abstract: Background: Considering the rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), the clinical implications of gastrointestinal (GI) and hepatic manifestations of coronavirus disease 2019 (COVID-19) in the U.S. population require analysis. Methods: We retrospectively reviewed all adult patients with COVID-19 admitted to our facility. Patients were divided into two groups based on the presence of GI symptoms and transaminitis at presentation. Univariable analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
2
Order By: Relevance
“…Therefore, we further reviewed the literatures in our analysis. Among the literatures that had data on the age of patients with/without GI symptoms, all of the European and American literatures (n = 8 of 8, 100%) [ 15 , 19 , 33 , 34 , 37 , 45 , 46 , 49 ] reported that patients with GI symptoms were younger than those without. And OR values were < 1 in 7 [ 15 , 19 , 33 , 34 , 37 , 46 , 49 ] of these 8 literatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we further reviewed the literatures in our analysis. Among the literatures that had data on the age of patients with/without GI symptoms, all of the European and American literatures (n = 8 of 8, 100%) [ 15 , 19 , 33 , 34 , 37 , 45 , 46 , 49 ] reported that patients with GI symptoms were younger than those without. And OR values were < 1 in 7 [ 15 , 19 , 33 , 34 , 37 , 46 , 49 ] of these 8 literatures.…”
Section: Resultsmentioning
confidence: 99%
“…Among the literatures that had data on the age of patients with/without GI symptoms, all of the European and American literatures (n = 8 of 8, 100%) [ 15 , 19 , 33 , 34 , 37 , 45 , 46 , 49 ] reported that patients with GI symptoms were younger than those without. And OR values were < 1 in 7 [ 15 , 19 , 33 , 34 , 37 , 46 , 49 ] of these 8 literatures. On the other hand, 7 [ 12 , 16 , 18 , 25 , 29 , 36 , 57 ] of 13 Asian studies [ 12 , 16 , 18 , 25 , 29 , 30 , 36 , 38 , 40 , 43 , 50 , 52 , 57 ] reported that patients with GI symptoms were older, and OR values were > 1 in 6[ 12 , 16 , 25 , 29 , 36 , 57 ] of these 7 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The studies summarized no significant difference in total bilirubin, AST, and ALT levels between patients with GI symptoms and those without COVID-19. [16,17] Furthermore, according to studies, the colon has similar ACE2 expression as the liver. The small intestine has a high level of expression than that in the liver, and the expression levels in the colon and small intestine vary Clinical Characteristics, Surgical Management And Outcomes Of Abdominal Pain Among SARS-COV-2 Infected Patients: A Chart Review compared to the liver and lung [18].…”
Section: Discussionmentioning
confidence: 97%
“…Those with increased transaminase levels on admission are more likely to develop hypoxia or severe inflammation (21). Furthermore, patients with elevated liver enzyme levels on admission or follow-up have an increased risk of life-threatening complications, ICU admission and death (22,23). Some authors reported increased CK levels and suggested associations of its elevation with poor prognosis in the course of COVID-19 (2,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with elevated liver enzyme levels on admission or follow-up have an increased risk of life-threatening complications, ICU admission and death [20] [21] . Some authors reported increased CK levels and suggested associations of its elevation with poor prognosis in the course of COVID-19 [2] [22] [23] .…”
Section: Discussionmentioning
confidence: 99%